2003
DOI: 10.1093/jnen/62.5.520
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Promotes the Proliferation of Adult Schwann Cells Isolated from Axotomized Sciatic Nerve

Abstract: We have previously found that adult Schwann cells express receptors for lysophosphatidic acid (EDG2, EDG7) and sphingosine-1-phosphate (EDG5) and that expression of these receptors is significantly upregulated in injured sciatic nerve coincident with postaxotomy Schwann cell proliferation. Based on these observations, we hypothesized that lysophosphatidic acid and/or sphingosine-1-phosphate promote Schwann cell mitogenesis in injured adult nerve. We found that both saturated and unsaturated forms of lysophosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…In adult SCs isolated from axotomized sciatic nerve, Lpar1 and Lpar2 are coincidentally upregulated during post-axotomy SC proliferation, suggesting that LPA signaling promotes SC division in regenerating peripheral nerves (Weiner et al, 2001; Frohnert et al, 2003). In contrast, exogenous LPA induces demyelination of neurons in dorsal root ex vivo culture as well as in mice that have been intrathecally injected with LPA (Inoue et al, 2004).…”
Section: Lparsmentioning
confidence: 99%
“…In adult SCs isolated from axotomized sciatic nerve, Lpar1 and Lpar2 are coincidentally upregulated during post-axotomy SC proliferation, suggesting that LPA signaling promotes SC division in regenerating peripheral nerves (Weiner et al, 2001; Frohnert et al, 2003). In contrast, exogenous LPA induces demyelination of neurons in dorsal root ex vivo culture as well as in mice that have been intrathecally injected with LPA (Inoue et al, 2004).…”
Section: Lparsmentioning
confidence: 99%
“…LPA's involvement in neurogenesis is now well established (Kingsbury et al 2003); yet less is known of its role in the adult nervous system. In vitro experiments performed on adult mouse cells demonstrated that LPA induces neurite retraction of dorsal root ganglion neurons (Bouquet et al 2007) and stimulates proliferation, process retraction and motility of Schwann cells (Bouquet et al 2007;Frohnert et al 2003). Following CNS injury or ischemia, LPA-like activity increases within the CSF Tigyi et al 1995) and levels of ATX increase within astrocytes neighboring a lesion of the adult rat brain (Savaskan et al 2007), suggesting a role for LPA in brain injury responses.…”
Section: Introductionmentioning
confidence: 99%
“…Less is known of its role in the adult nervous system. In studies performed in vitro on adult mouse cells, LPA stimulates the proliferation, process retraction and motility of Schwann cells (Bouquet et al 2007;Frohnert et al 2003) and induces neurite retraction of dorsal root ganglion (DRG) neurons (Bouquet et al 2007). Following injury or ischemia of the nervous system, LPA-like activity increases within the cerebrospinal fluid thus, LPA concentrations probably increase within the CNS because of the impairment of the blood-brain barrier (Eichholtz et al 1993;Tigyi et al 1995).…”
Section: Introductionmentioning
confidence: 99%